Assessing changes in ultraviolet radiation-exposed mouse skin using optical coherence tomography - Anna V. Vejlsby; Celina Pihl; Rozarin Delal Kara; Merete Haedersdal; Peter E. Andersen; Catharina M. Lerche; Gavrielle R. Untracht (PLoS ONE, 2025)
Skin cancer is one of the most common types of cancer, frequently resulting from excessive exposure to ultraviolet radiation (UVR). Early detection and effective prevention of photodamage are important to mitigate the long-term risks of skin cancer. In this study, we investigate the use of optical coherence tomography (OCT) for assessing photodamage over time and the efficacy of photodamage prevention treatments non-invasively. Of the n = 81 hairless mice, 75 of them were exposed to ultraviolet radiation (UVR) three times per week to induce photodamage. Two different systemic photodamage prevention treatments were tested: nicotinamide mononucleotide (NMN) and polypodium leucotomos (PL). OCT images were acquired monthly on the back, side, and stomach of the mice over 7 months. Two OCT-derived metrics, skin thickness and the attenuation coefficient, μOCT, were quantified using a custom-developed algorithm to evaluate photodamage. Significant differences in skin thickness (p = 0.038) and attenuation coefficient (p<0.001) were observed between the UVR control group and the non-irradiated control group after 7 months at the back. At month 7, no significant difference was observed in the attenuation coefficient between the UVR control group and the UVR + PL group, however, a significant difference was observed between the UVR control group and the UVR + NMN group. Additionally, our OCT-derived skin thickness was well correlated with the skin thickness measured from histology, demonstrating a strong alignment with these invasive ground truth findings. Altogether, our results indicate that OCT could be a useful tool for non-invasive monitoring of photodamage in skin and for monitoring the efficacy of photodamage prevention treatments.